5-(Sulfamoyl)thien-2-yl 1, 3-oxazole inhibitors of carbonic anhydrase II with hydrophilic periphery. (31st December 2022) - Kalinin, Stanislav; Kovalenko, Alexander; Valtari, Annika; Nocentini, Alessio; Gureev, Maxim; Urtti, Arto; Korsakov, Mikhail; Supuran, Claudiu T.; Krasavin, Mikhail
Abstract: Hydrophilic derivatives of an earlier described series of carbonic anhydrase inhibitors have been designed, prepared and profiled against a panel of carbonic anhydrase isoforms, including the glaucoma-related h CA II. For all hydrophilic derivatives, computational prediction of intraocular permeability routes showed the predominance of conjunctival rather than corneal absorption. The potentially reactive primary or secondary amine periphery of these compounds makes them suitable candidates for bioconjugation to polymeric drug carriers. As was shown previously, the most active h CA II inhibitor is efficacious in alleviating intraocular pressure in normotensive rabbits with efficacy matching that of dorzolamide. Graphical Abstract: UF0001